Efficacy and safety of hypoxia-inducible factor-prolyl hydroxylase inhibitor treatment for anemia in chronic kidney disease: an umbrella review of meta-analyses - Ren, Song; Yao, Xiaoxiu; Li, Yi; Zhang, Ying; Tong, Chao; Feng, Yunlin (Frontiers in Pharmacology, 2023)
The objective was to provide a comprehensive summary of existing evidence on the efficacy and safety of hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) for the treatment of anemia in chronic kidney disease (CKD). A systematic search was conducted in the Medline, Embase, and Cochrane databases. Only meta-analyses that evaluated the efficacy and safety of HIF-PHI treatment for anemia in CKD were included. The efficacy outcomes included hemoglobin levels and iron metabolism indices, while the safety outcomes were assessed by examining adverse events. The qualities of methodologies and evidence were assessed using the AMSTAR 2 system and the NutriGrade tool, respectively. Fourteen meta-analyses, comprising 105 distinct comparisons, were included. The comparisons were backed by evidence of high, moderate, and low levels, distributed in approximately equal proportions. None of the studies were deemed to possess a high level of confidence. In both the overall and individual treatment groups of HIF-PHI, there was an increase in the levels of hemoglobin, transferrin, and transferrin saturation, while the levels of hepcidin and total iron binding capacity decreased. Serum ferritin exhibited a reduction to some extent, while serum iron did not show significant alterations following HIF-PHI treatments. There were no notable disparities in safety outcomes between the HIF-PHI and erythropoietin stimulating agents or placebo groups. This umbrella review suggests that HIF-PHI treatment can effectively increase hemoglobin levels in CKD patients and enhance iron metabolism by decreasing hepcidin levels and improving iron transport. The safety profiles of HIF-PHIs were generally comparable to those of ESA therapies or placebos.